Andrografolid : Potensi Sebagai Antiaterosklerosis Pada Sitokin Il-1β - Putu Yudha Ugrasena; Iwan Saka Nugraha; Ni Wayan Rika Kumara Dewi (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
The focus is how the role of cytokines in atherosclerosis as a chronic inflammatory disease, as it is known that cytokines regulate complex inflammatory responses in atherosclerotic plaques, especially IL-1β. Sambiloto (Andrographis paniculata) is a plant with various pharmacological activities. Andrographolide (AND) is the main bioactive compound in the diterpene lactone group. This literature study aims to assess the potential of AND on the proinflammatory cytokine IL-1 β as an antiatherosclerosis. This type of research is a qualitative review of various studies using sambiloto plants or andrographolide compounds (AND). Search literature using the Google Scholar database. Keywords used "Andrographis paniculata, andrographolide, IL-1β, Atherosclerosis. The results showed that AND has effects as an anti-inflammatory, antiatherosclerosis as well as cardiovascular-related diseases. There are not many articles on the activity of AND in IL-1β against atherosclerosis, but AND can provide inhibitory activity of the cytokine IL-1β against inflammation. Not many researchers have discussed the pharmacological effects of AND as an antiatherosclerotic on IL-1β therapeutic targets, but from the results of the review AND has a strong potential in inhibiting IL-1 cytokine secretion β.